Fiscal policy: post- or New Keynesian? - Sebastian Gechert (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This paper asks whether the post-Keynesian or New Keynesian paradigm provides a more realistic description of the effects of fiscal policy on output and consumption. I establish some macro and microeconomic stylized facts on fiscal multipliers and marginal propensities to consume based on the extensive empirical literature. I compare them to basic and extended modelling approaches within the two traditions. The picture is mixed and points to shortcomings in both paradigms. I outline the elements they could learn from each other as well as from some other strands in the literature to create a coherent and convincing Keynesian macro-micro framework of fiscal policy modelling.
Keywords: D10; E20; E60; H30; 330; macroeconomics; fiscal policy; history of economic thought; multiplier; marginal propensity to consume